2002
DOI: 10.1128/jvi.76.20.10211-10218.2002
|View full text |Cite
|
Sign up to set email alerts
|

RU5 of Mason-Pfizer Monkey Virus 5′ Long Terminal Repeat Enhances Cytoplasmic Expression of Human Immunodeficiency Virus Type 1 gag-pol and Nonviral Reporter RNA

Abstract: Retroviruses utilize an unspliced version of their primary transcription product as an RNA template for synthesis of viral Gag and Pol structural and enzymatic proteins. Cytoplasmic expression of the gag-pol RNA is achieved despite the lack of intron removal and the presence of a long and highly structured 5 untranslated region that inhibits efficient ribosome scanning. In this study, we have identified for the first time that the 5 long terminal repeat ( Retroviruses need to subvert typical cellular posttrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…Further, the Tap protein could be immunoprecipitated from the polyribosome fractions of sucrose sedimentation gradients, indicating that Tap associates with polyribosomes (29). Similarly, cellular RNA helicase A (RHA) has recently been shown to enhance translation of retroviral RNAs containing a 5Ј-terminal posttranscriptional control element, found in avian spleen necrosis virus (5) and MPMV (25). RHA binds the highly structured posttranscriptional control element to mediate the translational enhancement (21).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the Tap protein could be immunoprecipitated from the polyribosome fractions of sucrose sedimentation gradients, indicating that Tap associates with polyribosomes (29). Similarly, cellular RNA helicase A (RHA) has recently been shown to enhance translation of retroviral RNAs containing a 5Ј-terminal posttranscriptional control element, found in avian spleen necrosis virus (5) and MPMV (25). RHA binds the highly structured posttranscriptional control element to mediate the translational enhancement (21).…”
Section: Discussionmentioning
confidence: 99%
“…PCE is a highly structured, orientationdependent motif present in the 59 UTRs of some retroviral mRNAs (Butsch et al 1999;Roberts and Boris-Lawrie 2000;Hull and Boris-Lawrie 2002). The 59PCE activity is positively regulated by RHA and is essential for the translation efficiency of viral mRNAs (Butsch et al 1999;Hull and Boris-Lawrie 2002). In addition, Hartman et al (2006) demonstrated that the PCE-like element in the 59 UTR of human JunD mRNA interacts with RHA and regulates translation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was demonstrated that RHA is a necessary cofactor to promote translation initiation of highly structured mRNAs containing the post-transcriptional control element (PCE) Zhang and Grosse 2004;Hartman et al 2006). PCE is a highly structured, orientationdependent motif present in the 59 UTRs of some retroviral mRNAs (Butsch et al 1999;Roberts and Boris-Lawrie 2000;Hull and Boris-Lawrie 2002). The 59PCE activity is positively regulated by RHA and is essential for the translation efficiency of viral mRNAs (Butsch et al 1999;Hull and Boris-Lawrie 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The 3Ј UTRs of avian leukosis virus and the related Rous sarcoma virus contain one and two copies, respectively, of a direct repeat (DR) element that is necessary for cytoplasmic accumulation and stability of unspliced viral RNA and for assembly of progeny virions (1, 22-24, 29, 30, 33). The 5Ј long terminal repeats (LTRs) of spleen necrosis virus (SNV) and MPMV contain a unique posttranscriptional control element that facilitates reporter gene expression from unspliced human immunodeficiency virus type 1 (HIV-1) gag reporter RNA independently of Rev/Rev-responsive element (RRE), and also nonviral luc RNA (6,15,28).Extensive mutagenesis studies of CTE and DR have mapped necessary and redundant structural motifs that present unpaired nucleotides for interaction with cellular posttranscriptional modulators. The MPMV and SRV-1 CTEs share 92% sequence homology and are 154-nucleotide (nt) orientationand position-dependent RNA elements (27, 32).…”
mentioning
confidence: 99%